Supply-Side Effects of Disinflation Programs - Roldos, Jorge (IMF Working Papers; Working Paper, 1994)
This paper focuses on the short-run and long-run supply-side effects of disinflation programs in a two-sector economy. Fixing the exchange rate reduces the wedge between the return on foreign assets and that on domestic capital, leading to an increase in the latter. After an initial real exchange rate appreciation and increase in the production of nontradables-due to a consumption boom-the new capital is gradually installed in the tradable sector. During this transitional period, further real appreciation takes place-as the expansion of the tradable sector pulls labor away from the nontradable sector-together with investment-driven deficits in the current account. We conclude that when appreciation and deficits are due to supply-side rigidities, rather than to credibility and/or price stickiness, no further policies (i.e., capital controls, incomes policies) are advisable.